2008
DOI: 10.1534/genetics.107.082768
|View full text |Cite
|
Sign up to set email alerts
|

Population Bottlenecks Increase Additive Genetic Variance But Do Not Break a Selection Limit in Rain Forest Drosophila

Abstract: According to neutral quantitative genetic theory, population bottlenecks are expected to decrease standing levels of additive genetic variance of quantitative traits. However, some empirical and theoretical results suggest that, if nonadditive genetic effects influence the trait, bottlenecks may actually increase additive genetic variance. This has been an important issue in conservation genetics where it has been suggested that small population size might actually experience an increase rather than a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 70 publications
3
54
0
Order By: Relevance
“…For example, Brewer et al (1990) found no correlation between the severity of inbreeding depression and the initial genetic diversity of mice population stocks. Increases in variance following bottlenecks have also been reported in Musca domestica (Bryant et al 1986;Bryant and Meffert 1993), Drosophila melanogaster (López-Fanjul and Villaverde 1989; García et al 1994;Van Heerwaarden et al 2008) and Tribolium castaneum (Fernández et al 1995;Wade et al 1996).…”
Section: Drift Effects On Quantitative Traits and Adaptive Potentialmentioning
confidence: 73%
“…For example, Brewer et al (1990) found no correlation between the severity of inbreeding depression and the initial genetic diversity of mice population stocks. Increases in variance following bottlenecks have also been reported in Musca domestica (Bryant et al 1986;Bryant and Meffert 1993), Drosophila melanogaster (López-Fanjul and Villaverde 1989; García et al 1994;Van Heerwaarden et al 2008) and Tribolium castaneum (Fernández et al 1995;Wade et al 1996).…”
Section: Drift Effects On Quantitative Traits and Adaptive Potentialmentioning
confidence: 73%
“…This is essentially because such effects are most influential in small, subdivided populations incurring strong selection (Wade, 2002), which are increasingly associated with global change (Gienapp et al., 2008; Jump & Penuelas, 2005; Moller, Rubolini, & Lehikoinen, 2008). Warming‐driven declines in population size, for example, could see greater conversion of nonadditive variance into additive variance (Barton & Turelli, 2004; Cheverud et al., 1999; Goodnight, 1988; Wang et al., 1998), although van Heerwaarden, Willi, Kristensen, and Hoffmann (2008) showed that increases in the latter during population bottlenecks do not necessarily improve adaptive capacity in Drosophila . Alternatively, greater expression of nonadditive genetic effects under warming might not only hinder adaptive capacity by masking favorable or unfavorable alleles from selection, but also hinder the erosion of additive genetic variance in doing so (Crnokrak & Roff, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…While our goal here was to draw attention to the size and environmental sensitivity of these effects, our work now highlights the need to better incorporate them into predictions of population persistence in changing environments. In particular, there is pressing need for studies that examine the stability of nonadditive genetic and maternal environmental effects across multiple generations (e.g., Dey et al., 2016; van Heerwaarden et al., 2008), that incorporate them into projections of population dynamics (e.g., Coulson, Tuljapurkar, & Childs, 2010), and that consider their effects in multiple or fluctuating environments. Such work is currently rare, but will enhance our ability to forecast the adaptive capacity of populations exposed to global change so they can be managed more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, theoretical models demonstrate that genetic bottlenecks have the capacity to increase additive genetic variation in affected populations -either by "converting" epistatic into additive variation via the fixation of some alleles due to drift (Goodnight 1988) or by increasing the frequency of rare recessive alleles at loci where dominance effects occur (Robertson 1952;Willis and Orr 1993). While some studies are consistent with such predictions (Bryant and Meffert 1993; Saccheri et al 2006), on the whole empirical evidence has been equivocal (van Heerwaarden et al 2008;Jarvis 2011;Dlugosch et al 2015) and primarily derived from limited laboratory studies.…”
Section: Key Mechanismsmentioning
confidence: 99%